Expanding the resource base of panchayats: augmenting own revenues - Rao, M. govinda; Rao, U.A. Vasanth (2008)
Fiscal decentralisation to rural local governments in India is meaningful only when the panchayats have adequate untied funds to provide public services assigned to them which require the assignment of tax powers. This paper shows that revenue mobilisation by rural local bodies is abysmally low. The assignment does not include any important revenue handles and the panchayats are not able to exploit properly even the only notable tax base assigned to them - the property tax. The paper argues that it is necessary to take a re-look at the tax powers of panchayats. It is also important to build administrative and enforcement capacity. An essential precondition for building such capacity is to create a reliable data and information system. - Reproduced.
Keywords: Panchayat - india; Panchayat